Debata konstytucyjna w Strefowej Radzie Doradczej w 1947 roku. - Bożek, Michał (Wydawnictwo Poznańskie sp. z o.o., 2011)
In February 1947, a Zonal Advisory Council with a seat in Hamburg was appointed in the British zone of postwar Germany. The Council worked for over two years and one of its main achievements was the organisation in the autumn of 1947 of a constitutional debate on the future of the German state. Its participants represented six German parties: the Christian-Democratic Union CDU, the Social Democratic Party of Germany SPD, the Free Democratic Party FDP, the Communist Party of Germany KPD, the Centre Party and the German Party. There were a number of projects proposed in the course of the debate. The project presented by the CDU did not gain universal recognition and was therefore reduced to being merely one of the concepts discussed in the course of the deliberations on the political regime of postwar Germany. The SDP, on the other hand, presented a project that it had been prepared already earlier and was presented as its official standpoint regarding the political structure of the German state after the war. Therefore, even if some time later the international situation changed and the basic concepts of the Party’s political strategy had to be revalued and a new project was to be drafted and submitted before the appointment of the Parliamentary Council, the official stance of the SDP contained in that project remained while the project itself constituted one of the elements of that political strategy.
CONSTITUTIONAL DEBATE IN THE ZONAL ADVISORY COUNCIL IN 1947.
Keywords: Niemcy; Strefowa Rada Doradcza; Debata konstytucyjna; 1947